STUDI TENTANG FAKTOR DAMPAK DAN INDEKS KECEPATAN PADA JURNAL ELEKTRONIK SOSIO HUMANIORA UNIVERSITAS PADJADJARAN - Winoto, Yunus; -, Rohanda (Edulib, 2017)
Abstract. Activities cite literature is an integral part of the activities of writing scientific papers. In the writing of a work in scientific journals either in the form of research results or other study results quoting the opinions of other authors contained in the same journal or different journals but still in a clump of the same science often coloring a writing. In citation analysis activities a scientific journal is known to exist several terms such as a speed index that is a measure to find out how quickly a group of documents or articles from a journal is cited in the same year and an impact factor that is a measure for the influence of an article in a journal in a given period. This study aims to examine the index of velocity and impact factors of articles published in the electronic journals (OJS) socio-humanities of Padjadjaran University. The method used in this research is quantitative descriptive method with research type of citation analysis. The period of the journal published human socio-humanities are jurnal period published 2012-2015 with the number of articles published 128 as many scientific articles. Based on the results of this study note that the index of the density and impact factors of the human socio journal of Universitas Padjadjaran is still low. This is apparent with the lack of articles published in the humanitarian socio journal of Padjadjaran University cited or dikutif by other authors in other imitation journals as well as scientific journals of the socio-humanities of UNPAD itself.